(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2018)
In this article we study the memories of the recent past in the School Nº 185 Coronel Álvarez Condarco of Paraná city (Entre Ríos province -Argentina). This institution was signposted in 2013, because it was a clandestine detention center (CDC) during the last dictatorship. Instead of that, the educative community resists to accept this fact. We analyze this case into the national history, using oral testimonies, class records, bibliography about this problem, testimonial literature, judicial and journalist sources.